Inovasi Pengolahan Ampas Tahu menjadi Tepung Guna Mendukung Ketahanan Pangan Nasional di Pabrik Tahu Pak Badrun - Yuniantari, Ni Luh Putu; Anjarsari, Dini Nastiti; Susilowati, Erlin (Kadiri University, 2025)
Solid waste from tofu production, commonly referred to as tofu dregs, has not been further processed by partners, in this case, the Pak Badrun Tofu factory. The tofu dregs produced by partners are only sold to cattle and goat farmers as animal feed. However, according to several studies conducted, it has been found that the nutritional value of tofu dregs is quite high; therefore, tofu dregs have great potential to be further processed into flour. A lack of knowledge about the use of tofu dregs in flour is one of the obstacles to processing tofu dregs, which could be utilized in other products with high economic value. The utilization of tofu dregs can provide economic and practical benefits in their processing. Additionally, processing tofu dregs can offer the community choices in terms of selecting flour with better nutritional content. Processing tofu dregs into flour can encourage the development of new processed products from tofu dregs, as a way to support food security and safety, ultimately improving community nutrition. In order to provide appropriate solutions to partners, the tofu dregs processing program is carried out in three stages, namely: 1) Conducting outreach on the production of flour from tofu dregs to partners, 2) Training on the production of flour from tofu dregs, and 3) Training in product management and digital marketing. This program successfully enhanced the knowledge, production skills, and digital marketing capabilities of participants, enabling them to process tofu dregs into value-added products with the potential to positively impact the community's economy in a sustainable manner. Limbah padat hasil produksi tahu yang biasa disebut sebagai ampas tahu belum diolah lebih lanjut oleh mitra dalam hal ini pabrik Tahu Pak Badrun. Selama ini ampas tahu yang dihasilkan dari proses produksi tahu hanya dijual ke peternak sapi dan kambing sebagai pakan ternak, padahal menurut beberapa penelitian yang telah dilakukan didapatkan bahwasanya ampas tahu memiliki kandungan gizi yang baik oleh karena itu ampas tahu memiliki potensi yang besar untuk dapat diolah lebih lanjut menjadi tepung. Kurangnya pengetahuan tentang pemanfaatan ampas tahu menjadi tepung merupakan salah satu kendala dalam upaya pengolahan ampas tahu yang seharusnya dapat dimanfaatkan menjadi produk lain yang memiliki nilai ekonomis tinggi. Pemanfaatan ampas tahu dapat memberikan keuntungan secara ekonomi dan praktis dalam pengolahannya selain itu dengan diolahnya ampas tahu dapat memberikan pilihan kepada masyarakat dalam hal memilih tepung dengan kandungan gizi yang lebih baik. Pengolahan ampas tahu menjadi tepung dapat mendorong munculnya produk olahan baru dari ampas tahu sebagai salah satu cara mendukung ketahanan dan keamanan pangan dalam hal ini adalah meningkatkan gizi masyarakat. Guna memberikan solusi tepat guna pada mitra maka program pengolahan ampas tahu dikerjakan dalam tiga tahapan yaitu; 1) melakukan Sosialisasi pembuatan tepung dengan berbahan dasar ampas tahu pada mitra, 2) Pelatihan Pembuatan tepung berbasis ampas tahu, 3) Pelatihan manajerial dan digital marketing produk. Program ini berhasil meningkatkan pengetahuan, keterampilan produksi, dan pemasaran digital peserta, sehingga ampas tahu dapat diolah menjadi produk bernilai tambah yang berpotensi meningkatkan ekonomi masyarakat secara berkelanjutan.